Different scaling and root planing strategies in Turkish patients with aggressive periodontitis: A randomized controlled clinical trial - DOĞAN, BAŞAK (My University, 2022)
Objectives The aim of this study was to compare clinical, cytokine and microbiological responses after quadrant-based scaling and root planing (Q-SRP), full-mouth SRP (FM-SRP) and full-mouth disinfection (FMD) in patients with generalized aggressive periodontitis (GAgP), which is currently termed as generalized stage-III and grade-C periodontitis. Methods Forty-two patients with GAgP were randomly assigned into groups as Q-SRP, FM-SRP or FMD with chlorhexidine. Clinical parameters were recorded, and gingival crevicular fluid (GCF) and subgingival plaque samples were collected at baseline, 3 and 6 months after treatment. GCF levels of interleukin (IL)-1 beta and IL-17 were analysed using ELISA. Quantities of six bacterial species were determined using qPCR. Results Clinical parameters improved significantly in all groups at 3 and 6 months (p 6 mm was lower in the FMD than Q-SRP group at 3 and 6 months (p < 0.05). FMD showed significantly higher percentage of pocket closure compared with Q-SRP and FM-SRP at both 3 and 6 months after treatment (p < 0.05). The IL-1 beta levels decreased only in the FMD group (p < 0.05), whereas no changes were found in IL-17 levels in any group. The levels of five out of six bacterial species decreased at 3 and/or 6 months only in the FMD group (p < 0.05). Conclusions The FMD treatment appears to offer superior outcome than Q-SRP and could be the first choice for patients with GAgP.
Keywords: Tıp; Sağlık Bilimleri; Diş Hekimliği; Medicine; Health Sciences; Dentistry; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Klinik Tıp; Klinik Tıp (MED); DENTISTRY, ORAL SURGERY & MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; aggressive periodontitis; bacteria; interleukin-1 beta; interleukin-17; periodontal debridement; FULL-MOUTH DISINFECTION; EARLY-ONSET PERIODONTITIS; PERI-IMPLANT DISEASES; ONE-STAGE; ULTRASONIC DEBRIDEMENT; CREVICULAR FLUID; CHRONIC ADULT; TH17 CELLS; THERAPY; CLASSIFICATION